Theories On Which Inclusive Education is Based and the View of Islam on Inclusive Religious Education - Karasu, Teceli (CUMHURIYET UNIV, FAC THEOLOGY, 2019)
In recent years in Turkey, it has been attempted to ensure that students who need special education are educated through inclusion. In the meanwhile, it became important to reveal scientifically the educational theories on which the inclusive education is based and the approach of Islam towards inclusive education that somehow has an influence on our national education policy. This study aims to examine the educational theories on which the inclusive education is based and the Islamic approach towards inclusive education. The data of the study was collected by literature review. As a result, it is possible to say that the underlying theories of inclusive education are integrated education theory, cognitive democrative theory and dysontogenesis theories. In addition, although there are no specific verses for inclusive education in the Qur'an and the Sunnah, it can be said that Islam has an positive approach to the inclusive education in general. Depending on this result, formal education should be conducted in the context of the principle of "least restricted education environment".
Keywords: Religious Education; Inclusive Education; Inclusive Theories; Inclusion Basics; Inclusive Religious Education